Human T cell leukemia virus type I tax enhances IL-4 gene expression in T cells - Li-Weber, Min; Krammer, Peter H. (European journal of immunology, 2001)
The human T cell leukemia virus type-1 (HTLV-1) is the etiologic agent of adult T cell leukemia (ATL). Since the HTLV-I-encoded transactivator Tax has been shown to activate many cellular genes including cytokine genes interleukin (IL-)1α , 2, 5, 6, 8, 10 and 15, we ask whether Tax also affects IL-4 expression. In this study, we show that addition of recombinant Tax proteins greatly enhances IL-4 secretion in human peripheral primary T cells. Transient transfection studies showed that ectopic expression of Tax significantly enhanced IL-4 promoter activity. The IL-4 promoter contains a strong NF-IL6 (PRE-I element) and a NF-AT/NF-κB overlapping site (P1 element). We show that expression of Tax stimulates NF-IL6 binding to the PRE-I element and, consequently, enhancesPRE-I-mediated transcriptional activity. Using Jurkat T cell lines which stably express Tax fused to the hormone binding domain of the human estrogen receptor (ER), we show that Tax enhances endogenous IL-4 mRNA expression and increases IL-4 promoter activity in a hormone-dependent manner. Mutation analysis revealed that the IL-4 PRE-I (NF-IL6 site) and the P1 (NF-AT/NF-κB site) are involved in Tax-mediated transactivation. Our studies provide the first evidence of the functional involvement of Tax in IL-4 gene regulation.